C1orf109L binding DHX9 promotes DNA damage depended on the R‐loop accumulation and enhances camptothecin chemosensitivity. (6th August 2020) - Dou, Peng; Li, Yiqun; Sun, Haoxiu; Xie, Wanqiu; Zhang, Xiaoqing; Zhang, Xiaohan; Zhang, Dandan; Qiao, Shupei; Ci, Yanpeng; Nie, Huan; Han, Fang; Li, Yu
Abstract: Objectives: R‐loop is a three‐stranded nucleic acid structure of RNA/DNA hybrid, which occurs naturally during transcription, and more R‐loop accumulation can trigger serious DNA damage. There has been increasing attention to the issue of R‐loop accumulation acted as a target for cancer therapy. However, the regulation of R‐loop‐associated proteins is poorly explored. Material and method: Quantitative real‐time PCR and Western blot were used to measure the expression of C1orf109 in cell lines. In addition, C1orf109L (C1orf109 longest isoform) protein binding partner was identified and validated using immunoprecipitation‐mass spectrometric (IP‐MS) and immunoprecipitation assays. DNA‐RNA immunoprecipitation (DR‐IP) and immunofluorescence determined the C1orf109L location on R‐loop. R‐loop accumulation was determined by immunofluorescence. Cell cycle was determined by flow cytometry. Finally, time‐lapse assay and cell counting were conducted to determined cell survival in response to camptothecin (CPT). Results: We found that C1orf109L could mediate cell cycle arrest in the G2/M phase and DNA damage depended on R‐loop accumulation. Meanwhile, C1orf109L could bind with DHX9 to trigger R‐loop accumulation. And C1orf109L was competitive with PARP1 binding to DHX9, which would block the function of DHX9‐PARP1 to prevent the R‐loop accumulation. Furthermore, C1orf109L could enhance the chemosensitivity of CPT, a chemotherapeutic drug capable of promoting R‐loop formation. Conclusions: Our data demonstrate that C1orf109L triggers R‐loop accumulation and DNA damage to arrest cell cycle. Abstract : C1orf109L could compete with PARP1 for DHX9 binding, which mediates DNA damage and cell cycle arrest via triggering R‐loop accumulation. Furthermore, C1orf109L could enhance the chemosensitivity of camptothecin, a chemotherapeutic drug capable of promoting R‐loop formation.